Research on the possibility of using stevia extract for production of ice cream of wellness orientation - Bazhay-Zhezherun, Svitlana; Telegin, Kiril (My University, 2013)
Методом ДФПГ , який базується на нейтралізації вільних радикалів, а саме α,α-дифеніл - β-пікрил гідразилу, визначено антиоксидантні властивості згущеного водного екстракту стевії. Встановлено, що досліджуваний зразок здійснює нейтралізацію вільного радикала ДФПГ на 66,6%. Встановлено оптимальну кількість внесення згущеного водного екстракту стевії для досягнення найкращих органолептичних та фізико-хімічних показників морозива. DFPH method, which is based on the neutralization of free radicals, namely α, α-diphenyl-β-pikryl hidrazyl, has determined the antioxidant properties of condensed aqueous stevia extract. It has been found that the sample neutralizes a free radical DFPH for 66.6%. An optimal amount of applying the condensed aqueous stevia extract for getting the best organoleptic and physico-chemical characteristics of ice cream has been found.
Keywords: ice-cream; antioxidant properties; extract of stevia; health feed; морозиво; антиоксидантні властивості; екстракт стевії; оздоровче харчування